CO2/pH-responsive particles with built-in fluorescence read-out. Issue 38 (6th September 2016) - Mabire, Anne B.; Brouard, Quentin; Pitto-Barry, Anaïs; Williams, Rebecca J.; Willcock, Helen; Kirby, Nigel; Chapman, Emma; O'Reilly, Rachel K.
Abstract : A novel fluorescent monomer was synthesized to probe the state of CO2 -responsive cross-linked polymer particles. Abstract : A novel fluorescent monomer was synthesized to probe the state of CO2 -responsive cross-linked polymeric particles. The fluorescent emission of this aminobromomaleimide-bearing monomer, being sensitive to protic environments, can provide information on the core hydrophilicity of the particles and therefore indicates the swollen state and size of the particles. The particles' core, synthesized from DEAEMA ( N, N -diethylaminoethyl methacrylate), is responsive to CO2 through protonation of the tertiary amines of DEAEMA. The response is reversible and the fluorescence emission can be recovered by simply bubbling nitrogen into the particle solution. Alternate purges of CO2 and N2 into the particles' solution allow several ON/OFF fluorescence emission cycles and simultaneous particle swelling/shrinking cycles.